Osallisuuden kokemuksia ja merkityksiä yläkoulun liikunnassa: ”koska se mitä tehdään niin kaikki tykkäisi ja olisi kivempaa, kun kaikilla olisi hauskaa” - Karttunen, Tomi; Koivukangas, Samuli (2018)
According to the national core curriculum values (OPS 2014, 15) uniqueness and growth of students must be supported by giving them experiences of being heard. Experiences of students’ participation and communality are also emphasized values in building the functions of community and in increasing wellbeing. The main purpose of the study was to find out what kind of experiences students in the eighth grade have had in their possibilities in influencing physical education. We also wanted to know how students would describe a physical education class of their dreams. The study examines students’ opinions about participation. The study was executed as a qualitative study and we collected the data by the open questionnaire. The qualitative data consisted of 40 eighth-grade students’ answers. The data was analyzed by using data-based content analysis. According to the study students have had most experiences of participation in the class in their choices of team and sport. Students felt that working together and the sense of community are meaningful in physical education. Students wanted to exercise in the way they would experience joy in physical education class of their dreams. Students also wanted to play games together as much as possible in the way that everybody is equally active. We also examined how the physical education classes would change if students were allowed to make more decisions in them. According to our study, most of the students felt physical education classes would be more fun if students could have more influence and make more decisions. Some students felt that decision-making would not necessarily be a good thing. These students felt that if students made most of the decisions in physical education classes, it would increase conflicts among students and there would be less variety in and between classes. According to our study teachers should take students’ opinions into consideration in planning. In addition students should have more possibilities in the decision-making process.